External Debt, Adjustment, and Growth - MARIANO, Roberto S. (Institutional Knowledge at Singapore Management University, 2006)
High ratios of external debt to GDP in selected Asian countries have contributed to the initiation, propagation, and severity of the financial and economic crises in recent years, reflecting runaway fiscal deficits and excessive foreign borrowing by the private sector. More importantly, the servicing of large debt stocks has diverted scarce resources from investment and long-term growth.